Transferência de calor em sistemas bifásicos durante a fusão térmica - Milito, Fernando Antonio (1978)
In this work a transient model of a free boundary value problem is analysed in arder to represent the temperature profile in liquid and solid phases during thermal fusion. The experimental results which were obtained in a special probe are compared with the results of the conductive unidirectional model in arder to determine the dynamical behavoir of the fusion front. The efficiency of the thermal process is also anklised with respect to its maximizing conditions as a function of the metal's physical properties, mainly its latent heat.